(untitled) (Revista de Biología Marina y Oceanografía, 2022)
In this study the enrichment dietary effect with different crude protein levels (CP) and feed additives on growth, survival, feed conversion ratio (FCR), feed consumption (FC) and total hemocyte count (THC) in juvenile white shrimp Litopenaeus vannamei were evaluated. The study covered two bioassays: in the first one, juveniles were daily fed for 45 days with four experimental diets containing: (1) Control, commercial feed (35% CP); (2) 29% CP; (3) 32% CP; (4) 35% CP. After the 29% CP diet was selected, juveniles in bioassay II were daily fed for 45 days with a single CP diet complemented with probiotics: (1) Control, commercial feed (35% CP); (2) 29% CP; (3) 29% CP + Bacillus mix at 1×106 CFUg–1 feed; and (4) 29% CP + yeast mix at 1×106 CFUg–1 feed. Juvenile shrimp fed with experimental diets gained significantly more weight and increased survival, FCR, FC and THC compared with control diet. However, differences among experimental diets were not significant. In bioassay II, juvenile shrimp fed with experimental diet + feed additives significantly increased survival, FCR, FC and THC compared with control diet. Growth of juveniles significantly increased with 29% CP and 29% CP + yeast mix diets, compared with control group. Complementing the diet with yeast mix showed higher survival and THC of juveniles compared with the other experimental treatments. Different CP levels in shrimp diet improved growth, survival and circulating hemocytes, and addition of mixed yeast as feed additive induced better survival and immune response in juvenile shrimp.